Cross-border reproductive services: suggestions for ethically based minimum standards of care in Europe - Thorn, Petra; Wischmann, Tewes; Blyth, Eric (Journal of psychosomatic obstetrics and gynecology, 2012)
Cross-border reproductive services (CBRS) is a phenomenon discussed worldwide. The major challenges associated with CBRS are the lack of data on the number of patients travelling for treatment and lack of transparency regarding the quality and safety of treatment procedures, especially in countries that have not yet introduced legislation or binding professional guidelines. This has given rise to practices that range from dubious to irresponsible treatment. Given that pan-European (let alone globally encompassing) legislation or guidelines are unlikely to appear quickly if at all, the authors suggest the implementation of ethically based minimum standards of care to which clinics and service providers can adhere on a voluntary basis. Such minimum standards of care can result in providing infertility treatment that is transparent, accountable and carried out responsibly for all parties involved.
Gesehen am 23.05.2018